The determinants of the success of microenterprise: a case study of BRI clients in Medan City, Indonesia - Hawariyuni, Weni; Mat Ghani, Gairuzazmi; Mat Derus, Alias (Faculty of Business Management, UiTM, 2014)
This study focuses on the determinants of the success of microenterprise owners in receiving loan from one of the successful microfinance institutions in the world, namely BRI Unit in Medan city, North Sumatra, Indonesia. This study applies the methodology before and after approach for measuring the success. It utilizes some financial indicators to measure the success of the microenterprises such as income, fixed assets, and household expenditures. The findings found financing in terms of amount of loan accessed has positive relationship with success indicators in terms of changes in income and fixed assets. However, it does not have positive relationship with changes in household expenditures. In the meantime, firm characteristics in terms of dummy variable for type of business of food and household facilities and necessities have positive relationship with changes in income. In conclusion, financing, firm characteristics, and household characteristics are the factors that determine the success of microenterprise in terms of income, fixed assets, and household expenditures. It is expected that policy makers of microfinance institutions (MFIs), including BRI Unit and Indonesian government could solve the common problems faced by MSMEs such as financing, raw materials, marketing, advanced technology, and others, as MSMEs play crucial role in increasing economic growth in terms of reducing poverty and unemployment; and increasing GDP. In this respect, policy makers of MFIs including BRI Unit is also expected to provide the facilities besides credit services such as training, health programs, education, family planning, and other programs to render greater effectiveness of the microfinance on the performance of microenterprise.